Hookworm Infection in South American Fur Seal (Arctocephalus australis) Pups: Pathology and Factors Associated With Host Tissue Damage and Mortality. (March 2017) - Seguel, M.; Muñoz, F.; Navarrete, M. J.; Paredes, E.; Howerth, E.; Gottdenker, N.
Tissues of South American fur seal pups naturally infected with hookworms ( Uncinaria sp ) were examined. Hookworm infection was found in nearly all pups examined (132/140, 94%), and hookworm enteritis with secondary bacteremia was considered the cause of death in 46 (35%) pups. Common findings in these pups included severe hemorrhagic enteritis and numerous (mean intensity = 761.8) hookworms in the jejunum. Hookworms were recovered from the abdominal cavity in 12 of 55 pups (22%) examined through peritoneal wash; these pups had an average of 1343.3 intestinal hookworms and marked fibrinohemorrhagic peritonitis. In all pups that died as a consequence of hookworm infection, the intestinal villi were short, blunt, and fused, and there were variable numbers of free and intrahistiocytic gram-negative bacteria in submucosal hookworm feeding tracks, mesenteric lymph nodes, spleen, blood vessels, and liver sinusoids. Pups that died of causes unrelated to the hookworm infection (trauma) had hookworm feeding tracks confined to the apical portions of the mucosa, and moderate to marked catarrhal eosinophilic enteritis. The number of hookworms was negatively correlated with intestinal villous length and number of leukocytes in the intestine. Pups with hookworm peritoneal penetration had nematodes with little or no blood in the hookworm intestine, suggesting that lack of food for the nematode could be associated with peritoneal penetration. Findings suggest that the initial burden of larval infection, the level of the host tissue response, or a combination determine the number of nematodes in the intestine, the severity of hookworm tissue damage, and pup mortality.